PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR - Subhan Subhan; Denny Kurniadi (Universitas Negeri Padang, 2019)
This Article describes how to develope of interactive learning media, that it can be used in teaching and learning activities in school. This development aims to design an Interactive Learning media that is suitable for Komjardas (Komputer dan Jaringan Dasar) in Vocational Schools. The method used is the Instructional Development Institute (IDI), namely by determining the principle of the system approach which includes three stages including define, develop, and evaluate. Interactive learning media is designed using Lectora Inspire Software, Adobe Flash Cs 6 and Wondershare Quiz Creator that function as makers of evaluation questions. The results of designing instructional media in the form of an application that can be run on all computers / laptops of each student.Keywords: Interactive Learning Media, Instructional Development Institute (IDI).